DIGITAL AND TECHNOLOGY-ENHANCED LEARNING IN ISLAMIC RELIGIOUS EDUCATION: A SYSTEMATIC LITERATURE REVIEW OF PEDAGOGICAL OUTCOMES, MECHANISMS, AND EVIDENCE STRENGTH - Retoliah; Fitri Ariati; Atna Akhiryani (Academic Bright Collaboration, 2026)
This systematic literature review examines the reported pedagogical outcomes and evidence strength of digital and technology-enhanced learning in Islamic Religious Education (IRE), with particular attention to how digital interventions operate across educational contexts, mechanisms, and outcomes. Using PRISMA procedures, this study reviewed Scopus-indexed articles published between 2018 and 2025. Forty-three studies meeting the inclusion criteria were synthesized through the CIMO framework, covering Context, Intervention, Mechanism, and Outcome. The studies generally reported promising short-term improvements in cognitive achievement, reflective thinking, interpretation literacy, worship-related motivation, learner engagement, teacher TPACK, and digital competence. However, because many included studies used short-term interventions, self-reported data, or designs with limited control of confounding variables, these findings should be interpreted as indicative rather than conclusive evidence of sustained pedagogical effectiveness. The findings are limited by the dominance of short-term studies, self-reported data, and Scopus-based coverage, which may underrepresent regional and non-indexed scholarship. This review contributes a CIMO-based synthesis of digital IRE and identifies TPACK+E, digital tabayyun, and scholarly oversight of AI as conceptual directions emerging from patterns across the reviewed studies for ethically grounded Islamic digital pedagogy.